NorthStar 5. Listening and speaking - Preiss, Sherry (Longman, 2009)
These CDs present level 5 of a 5 level series in two complimentary "strands" on English language learning. These CDs are part of the "Listening and speaking" strand, which takes a structured approach, which gives students opportunities for more extended and creative oral practice, for example, presentations, simulations, debates, speeches, public service announcements and more. There is enhanced focus on academic skills, more purposeful integration of critical thinking, and an enhanced focus on academic skills such as inferencing, synthesizing, notetaking, and test taking help students develop strategies for success in the classroom and on standardized tests.